2018
DOI: 10.1002/jssc.201800338
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantification of aloin A and B in aloe plants and aloe‐containing beverages, and pharmaceutical preparations by microchip capillary electrophoresis with laser induced fluorescence detection

Abstract: A microchip capillary electrophoresis coupled with laser induced fluorescence detection method for the fast determination of aloin was developed and comprehensively applied for the quantification of aloin A and B present in seven aloe plant species, 42 aloin-containing crude drugs, ten aloe pharmaceutical preparations, and four aloe gel-containing functional foods. The excitation and emission wavelengths for detection of both aloins were set at 473 and 520 nm, respectively. Sample analysis on a 35 mm length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…An increasingly common approach to increase the resolution between racemic natural products is the addition of cyclodextrins to a running buffer, such as chiral selectors. In addition, microchips are also becoming a popular strategy [ 22 ]. In the determination of arecoline by Xiang et al, the additive IL, 1–butyl–3–methylimidazolium tetrafluoroborate (BMImBF 4 ) was responsible not only for improvement of separation selectivity but also in the detection sensitivity of the analyte.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasingly common approach to increase the resolution between racemic natural products is the addition of cyclodextrins to a running buffer, such as chiral selectors. In addition, microchips are also becoming a popular strategy [ 22 ]. In the determination of arecoline by Xiang et al, the additive IL, 1–butyl–3–methylimidazolium tetrafluoroborate (BMImBF 4 ) was responsible not only for improvement of separation selectivity but also in the detection sensitivity of the analyte.…”
Section: Resultsmentioning
confidence: 99%
“…In a reported paper by Xiao at al., a developed and carefully applied MCE–LIF method for the fast quantification of aloin A and B present in seven aloe plant species and pharmaceutical formulations was presented. In this instance, the LOQ is expressed in ng mL −1 [ 22 ]. Table 1 shows that in many cases, UV detectors are sufficient for the analysis of active constituents in pharmaceutical formulation or herbal raw material.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonication and UAE are the most widely used extraction techniques in most publications to extract active components from various TCMs. For example, TCMs such as Chinese coptis (Yaroshenko et al, 2016), Macleaya cordata seeds, the herb Chelidonium majus (Sun et al, 2015), Flos Daturae (Ye et al, 2013a), Pollen Typhae (Han et al, 2012), Cuscuta chinensis Lam (Liu et al, 2016), Coreopsis tinctoria (Deng et al, 2017), Yufeng Ningxin-Radix Puerariae, the dry root of Pueraria lobata, Yufeng Ningxin tablet, Gegen soup granules, Gegen Zhiju soft capsules (Guo et al, 2019), aloe plants and aloe-containing beverages (Xiao et al, 2018), Valeriana (Li et al, 2014), and Forsythiae Fructus fruits (Gan et al, 2012) have all reported ultrasound methods for extraction. Bao et al compared two extraction methods with ultrasonication following basification to extract aconitum alkaloids from the dried root of Radix Aconiti (Bao et al, 2011).…”
Section: Ultrasonication and Ultrasonic Assisted Extraction (Uae)mentioning
confidence: 99%
“…MCE combined with LIF detection showed improved detection limits compared to UV detection. Xiao et al showed a rapid estimation of two anthraquinones (aloin A and B) in a variety of aloe plants in 40 s with cross-channel microchip CE paired with LIF detection (Xiao et al, 2018).…”
Section: Cze Analysis Of Flavonoids Anthraquinones and Terpenoidsmentioning
confidence: 99%
See 1 more Smart Citation